REALITAS PERNIKAHAN BEDA AGAMA PERSPEKTIF IBNU HAZM - Alfa Thoriqotur Rizqi, Qurrotul Ainiyah (UAS PRESS, 2022)
Islam emphasizes the virtue of finding a partner who is of the same religion. However, the reality in society is that interfaith marriages are still carried out by Muslims with non-people of the book. Responding to the interfaith marriage, Ibn Hazm allowed if the marriage was carried out by Muslims and people of the book. This study uses a qualitative method (library research). With the results: 1. Muslim women are not allowed to marry non-Muslim men either from among the polytheists or the people of the book. Muslim men may marry non-Muslim women from among the people of the book only. On the grounds that the people of the scriptures are not polytheists, because the religion of the people of the scriptures does not have any teachings about shirk. 2. In the Indonesian context, the opinion of Imam Ibn Hazm cannot be applied. Because interfaith marriages, especially Muslim men with Christian women, are feared to be a means of Christianizing Muslims and there are many benefits and harms than benefits for both parties and their descendants